Stolen Youth: The Politics of Israel’s Detention of Palestinian Children by Catherine Cook, Adam Hanieh, and Adah Kay (London and Sterling, VA: Pluto Press, in association with Defence for Children International: Palestine Section, 2004. 197 pages.) (American Journal of Islam and Society, 2006)
The subject of child detention is fraught with complexities of both a legaland an emotional nature, particularly when placed in the context of conflict. Founded on the Defence for Children International: Palestine Section’s(DCI/PS) work conducted between 1999 and 2003, the contributors developeda level of expertise in the realm of youth detention in Israeli prisonsthrough research, advocacy work, and the experiences of their colleagues,many of whom were former child detainees. The result is a compelling andoften disquieting read, replete with testimonies by the children, their families,and lawyers which relates the unforgiving conditions and obstacles thatclutter the legal process and place the child at a disadvantage.Edifying and cogent, the authors maintain an objective narrativethroughout, thereby enabling the reader to absorb the circumstances andlegal framework prior to constructing an independent conclusion. In addition,the tables, graphs, and figures corroborate and clarify such subjects asIsraeli position abuse (shabeh), the characteristics of prisons, and key termsrelated to human rights and humanitarian law, as well as a glossary that providesbackground information concerning the noted organizations, statutes,and terminologies ...